Insights of Early Blight of Tomato in Punjab - Gill, Enampreet Kaur; Kumar, Rajnish; Kaur, Anmol Preet; Pandey, Himanshu (International Journal of Economic Plants, 2025)
The experiment was conducted during rabi 2024 (February–April) at P.G. Department of Agriculture, Khalsa College, Amritsar to study disease level and epidemiological factors for accessing early blight of tomato, incited by Alternaria solani. A periodic survey of early blight of tomato was carried out in two districts of Punjab, namely Amritsar and Gurdaspur in the months of March–April, 2024. Disease incidence and disease severity were calculated at 6 places. The disease incidence of early blight of tomato ranged from 10.00 to 35.00% while, disease severity ranged from 9.67 to 26.66%. Maximum disease incidence of 35.00% was recorded in Loharka Kalan while minimum of 10.00% was observed in Balpurian. In case of disease severity, maximum was observed in Loharka Kalan (26.66%) while, minimum was observed in Balpurian (9.67%). Overall data indicated that the disease intensity was higher in Amritsar district than Gurdaspur district. The culture of Alternaria solani was blackish grey or whitish grey with a tint of olive green. The mycelium of the fungus was profusely branched and septate with hyaline to light brown colour. The development of early blight of tomato in relation to weather parameters was also observed. Results showed that maximum temperature, minimum temperature and wind speed are positively correlated with PDI whereas, rainfall and relative humidity are negatively correlated.